Statistical and geographical study on demolished buildings. Issue 1 (2nd January 2016) - Huuhka, Satu; Lahdensivu, Jukka
Abstract : Demolition of buildings is one fundamental, but little studied, factor in the dynamics of building stocks. This research study examines the characteristics and location of demolished buildings in Finland as well as motives behind the demolition decisions. A statistical and geographical analysis was performed on a dataset of all 50 818 buildings demolished in Finland between 2000 and 2012. In the Finnish context, the study shows that the amount of demolition, the size of the community, demographic development and construction activity are all interconnected. In general, the larger the community, the more it gains inhabitants and the more is built as well as demolished. The data confirm that removals from the building stock are a result of conscious deliberation. Non-residential buildings dominate the amount of demolished floor area. In addition, they are much larger and younger at the time of demolition than residential buildings, which consist primarily of detached houses. Demolitions are geographically concentrated: cities account for 76% of demolished floor area; and city cores for as much as 44%. Public policy needs to include demolition to reduce environmental impacts and improve resource efficiency.